The Open Biodiversity Knowledge Management System in Scholarly Publishing - Viktor Senderov (Research Ideas and Outcomes, 2016)
This project aims to develop and implement novel ways of publication, visualization, and dissemination of biodiversity and biodiversity-related data and thus bring the Open Biodiversity Knowledge Management System closer to fruition. In order to do so, we will develop new types of Enhanced Publications (EP's), which will allow automated data import into the manuscript and export from the manuscript and provide dynamic visualizations. These EP's will enable biodiversity researchers and taxonomists to streamline their work and publish more data-rich species descriptions.